Sodium-glucose transporter 2 inhibitors and cardiovascular-kidney-metabolic syndrome: a narrative review - Yuqing Wang; Yaqing Wang; Xiaojie He; Xiaodong Li (Frontiers in Endocrinology)
The Cardiovascular-Kidney-Metabolic (CKM) syndrome is a systemic disorder involving obesity, diabetes, chronic kidney disease (CKD), and cardiovascular disease, characterized by complex pathophysiological mechanisms that interact and lead to increased morbidity and mortality. In recent years, sodium-glucose transport protein 2 inhibitors (SGLT2i), as a new class of antidiabetic medications, have shown remarkable efficacy in the management of diabetes, renal and cardiovascular diseases. Research has confirmed their ability to reduce cardiovascular events and all-cause mortality. These inhibitors lower blood glucose levels by decreasing renal reabsorption of glucose and sodium, and offer multiple benefits, including lowering blood pressure, reducing body weight, exerting antioxidant, anti-inflammatory, and anti-fibrotic effects, as well as reducing proteinuria and improving glomerular filtration rate. These effects collectively contribute to the improvement of cardiovascular and renal health. Furthermore, SGLT2i have shown potential therapeutic roles at various stages of CKM syndrome, including improving cardiac function, slowing CKD progression, promoting weight loss, and improving lipid profiles. However, the precise mechanisms of action and off-target effects of SGLT2i still require further investigation to evaluate their efficacy and safety under different clinical conditions. Future research directions should include strategies for multiple disease management, combination therapy effects, interdisciplinary collaboration, and long-term follow-up studies to fully understand and optimize the application of SGLT2i in the treatment of CKM syndrome.